The frequency of complementary and integrative medicine methods in headache patients and their spending habits - Polat, Burcu; Saatçi, Özlem; Helvacı Yılmaz, Nesrin; Arıcı Düz, Özge (Elsevier Urban & Partner Sp Z O O, 2018)
Background: It is known that complementary and integrative medicine (CIM) methods are especially used by patients with chronic headaches. The aim of our study is to increase the knowledge on this topic, to provide objective data about use in Turkish headache patients. Methods: This study included 425 patients with headache. The survey form prepared was filled in under the supervision of a health professional. The questionnaire included 2 items, about CIM methods and finance. Results: Among the patients evaluated, 316 were female, and 109 were male. All of 52% answered yes to the question "did you ever use any CIM treatment method for headaches during your life?". The most frequently used methods were combined (herbal + one or more other method) (29.6%), herbal (9.4%) and cupping therapy (4.2%). Among the patients that used combined methods, 26.9% had spent 30-100 TL (5-25 euro), 20.6% had spent 100-300 TL (25-70 euro), 26.9% had spent 300-500 TL (70-120 euro) and the last two groups that formed 12.6% had spent 500-1000 (120-250 euro) and >1000 TL (>250 euro). Conclusion: Half of the patients that applied to outpatient clinic with headaches use one or more of these methods and make budgets in accordance with their income levels. Physicians should have sufficient knowledge and clinical opinions about the CIM methods used by headache patients.
WOS: 000446399100006
PubMed ID: 29306601
Keywords: Complementary and Integrative Medicine; Headache; Spending Habits